ANALYSIS OF DC HWI BLITAR INCOME STATEMENTS - Renny Rahayu; Diana Elvianita Martanti (JOSAR (Journal of Students Academic Research), 2020)
Financial statements can provide important information regarding financial position, financial performance, and capital changes. The purpose of this study is to analyze the preparation of income statements in DC. HWI Blitar. This research uses descriptive qualitative research with primary and secondary data sources. The results of the analysis and tracking of DC HWI Blitar regarding the preparation of the income statement obtained the conclusion that in preparation of the income statement on the DC HWI Blitar there are still some incompatibilities. It can be seen from the existence of errors and discrepancies in the presentation of accounts on the income statement presented by DC HWI Blitar for the period ending December 31, 2018, resulted in an understated valuation (reported too low). It reflects the assessment of DC HWI Blitar's income statement for the period ending December31, 2018 which has not been presented yet to show a fair valuation.